Xylooligosaccharide Modulates Gut Microbiota and Alleviates Colonic Inflammation Caused by High Fat Diet Induced Obesity - Fei, Yanquan; Wang, Yan; Pang, Yilin; Wang, Wenyan; Zhu, Dan; Xie, Meigui; Lan, Shile; Wang, Zheng (Frontiers in Physiology, 2020)
Obesity leads to colonic inflammation and may increase the risk of colorectal cancer. Xylooligosaccharide (XOS) exhibits strong antioxidant and excellent antibacterial properties, and can be utilized by gut microbes to maintain the ecological balance of the intestinal tract. In this study, we explored how XOS modulates the microbiota and regulates high fat diet (HFD) induced inflammation. We measured the changes in body weight and visceral coefficients in rats fed a high-fat diet. We also measured the expression levels of inflammatory factors in the plasma and colonic tissues of the rats using the enzyme-linked immunosorbent assay and real-time quantitative polymerase chain reaction. We analyzed the composition of fecal microorganisms and short chain fatty acid (SCFA) content using 16S rDNA and GC-MS. We found that XOS significantly counteracted HFD induced weight gain. Moreover, the plasma levels of monocyte chemoattractant protein-1, tumor necrosis factor (TNF-α) and lipopolysaccharide decreased in the XOS-treated rats. XOS treatment decreased TNF-α mRNA expression and increased occludin mRNA expression in the rat colon. We observed a reduction in the overall microbial abundance in the feces of the XOS-treated rats, although the proportion of Bacteroidetes/Firmicutes increased significantly and the number of beneficial bacteria increased in the form of dominant microbes. We found that both SCFA-producing bacteria and SCFA content increased in the gut of the XOS-treated rats. We identified a correlation between the abundance of Prevotella and Paraprevotella and SCFA content. Taken together, we propose that XOS can alleviate colonic inflammation by regulating gut microbial composition and enhancing SCFA content in the gut.